Facial Nerve Reconstruction and Facial Disfigurement after Radical Parotidectomy - Yla-Kotola, Tuija; Goldstein, David P.; Hofer, Stefan O. P.; Patel, Samip N.; Brown, Dale H.; Irish, Jonathan C.; Gullane, Patrick J.; Gilbert, Ralph (Journal of Reconstructive Microsurgery, 2015)
Background The importance of facial contouring with facial nerve reconstruction following total and radical parotidectomy is often overlooked. The goal of this study was to quantify the level of facial disfigurement and nerve dysfunction following reconstruction of the facial nerve, with or without reconstruction of the contours, using free tissue transfer.Methods A total of 26 patients with radical parotidectomy and facial nerve reconstruction were included in this retrospective study. Of the 26 patients, 15 underwent follow-up interviews and evaluation of facial nerve function and disfigurement using three different scales: the regional House-Brackmann (H-B) scale, the Facial Clinimetric Evaluation (FaCE) Scale, and the observer-rated disfigurement scale.Results Of the 15 evaluated patients, 8 patients underwent free tissue transfer. Mean follow-up time was 39 months (median, 35; range, 11–65 months). Of the 15 patients, 10 patients had good or moderate function according to the H-B mouth scale (median score, 4; range, 2–5), and satisfactory eye closure was observed in 10 patients (median score, 3; range, 2–5). The mean disfigurement value rated by the physician was 5 (scale, 1–9), with a mean patient rating of 4. Subjective total FaCE score varied significantly (mean, 52; range, 13–93).Conclusions Facial nerve and soft tissue reconstruction are highly beneficial to patients undergoing radical parotidectomy.
Keywords: facial nerve; nerve reconstruction; nerve graft; parotidectomy